Nifedipine-sensitive vascular reactivity of femoral arteries in WKY: the effects of pertussis toxin pretreatment and endothelium removal - Líšková, S; Kunes, J; Zicha, J (Physiological research, 2007)
Maintenance of norepinephrine (NE)-induced contraction is dependent on Ca(2+) influx through L-type voltage-dependent Ca(2+) channels (VDCC), which is opposed by nitric oxide. Adrenergic receptors are coupled with different G proteins, including inhibitory G proteins (Gi) that can be inactivated by pertussis toxin (PTX). Our study was aimed to investigate the effects of endothelium removal, PTX pretreatment and acute VDCC blockade by nifedipine on the contractions of femoral arteries stimulated by norepinephrine. We used 12-week-old male WKY, half of the rats being injected with PTX (10 microg/kg i.v., 48 h before the experiment), which considerably reduced their blood pressure (BP). Contractions of isolated arteries were measured using Mulvany-Halpern myograph. NE dose-response curves determined in femoral arteries from PTX-treated WKY rats were shifted to the right compared to those from control WKY. On the contrary, removal of endothelium augmented NE dose-response curves shifting them to the left. Acute VDCC blockade by nifedipine (10(-7) M) abolished all differences in NE dose-response curves which were dependent on the presence of either intact endothelium or functional Gi proteins because all NE dose-response curves were identical to the curve seen in vessels with intact endothelium from PTX-treated animals. We can conclude that BP reduction after PTX injection is accompanied by the attenuation of NE-induced contraction of femoral arteries irrespective of endothelium presence. Moreover, our data indicate that both vasodilator action of endothelium and Gi-dependent vasoconstrictor effect of norepinephrine operate via the control of Ca(2+) influx through VDCC.
Keywords: GTP-Binding Protein alpha Subunits, Gi-Go; Animals; Vasoconstriction; vztah mezi dávkou a účinkem léčiva; Endothelium, Vascular; vazokonstrikce; Femoral Artery; potkani inbrední WKY; vápníkové kanály; Nifedipine; blokátory kalciových kanálů; noradrenalin; proteiny vázající GTP - alfa-podjednotky Gi-Go; nifedipin; Calcium Channels; Rats, Inbred WKY; krevní tlak; Dose-Response Relationship, Drug; Male; Vasoconstrictor Agents; Calcium Channel Blockers; Norepinephrine; Pertussis Toxin; krysa rodu Rattus; cévní endotel; vazokonstriktory; oxid dusnatý; pertusový toxin; zvířata; mužské pohlaví; Blood Pressure; arteria femoralis; Rats; Nitric Oxide